Claim For Extension of Time and Additional Work Reviewed From the Aspect Construction Law and Contract - Elfriandi, Elfriandi; Sami’an, Sami’an; Hardjomuljadi, Sarwono (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
The purpose of this research is to determine that during the implementation period of the construction work of the Sintang 3 x 7MW coal-fired power plant from start to finish, several disputes related to legal and contractual aspects have occurred between the Contractor and the Owner throughout the implementation of the Sintang 3 x 7 MW Project from 2011 to 2014. Method This research is conducted using a normative-empirical approach, which is an approach that combines elements from both methods. Specifically, normative legal research is a process of discovering legal rules, legal principles, or legal doctrines to address the legal issues at hand. Empirical legal research is legal research that uses data obtained directly from its source.Claim results, The contractor is entitled to their rights based on legal aspects and the work of contract for the extension of time, namely; (1) delay in the start of work and site allocation; (2) delay due to the approval of the turbine generator vendor; (3) delay due to justification for changing the foundation type; (4) delay in the approval of the pump equipment vendor; (5) delay due to extreme heavy rain occurring every day. Meanwhile, for claims related to additional work (variation order), there is only one claim, which is the change in foundation type from swallow pile foundation to bored pile foundation, resulting in changes in unit price and quantity of the foundation. Therefore, it can be concluded that construction work is a job that involves many risks from a technical aspect, namely design, execution, and maintenance, which ultimately has the potential to lead to claims from the Contractor to the Owner.